The Implementation of “E-Manajemen Penyidikan” in Increasing Crime Clearance to Reduce Crime Percentage - Daniswara, Prasna (Indonesian National Police Academy, 2024)
This study examines the impact of the E-Manajemen Penyidikan (E-MP) system on crime clearance rates. The E-MP system, a web-based application, is designed to streamline investigative processes and enhance the efficiency of law enforcement agencies. Analyzing the findings through suitable theories; Management Information System, Legal Certainty, and Perkabareskrim No.1 of 2022. Employing a qualitative research approach, this study explores the experiences of police officers in utilizing the E-MP system. The findings suggest that the E- MP system has the potential to significantly improve crime clearance rates by facilitating data- driven decision-making, enhancing collaboration among investigators, and streamlining administrative tasks. However, the successful implementation of the E-MP system hinges on factors such as adequate training, technical support, and supportive organizational culture. This study contributes to the growing body of research on the use of technology in law enforcement and provides valuable insights for policymakers and practitioners seeking to improve the effectiveness of criminal investigations.